Pediatric Collections: Social Determinants of Health (Part 3: Promoting Health Equity) 2022
DOI: 10.1542/9781610026390-part03-screening_children
|View full text |Cite
|
Sign up to set email alerts
|

Screening Children for Social Determinants of Health: A Systematic Review

Abstract: CONTEXT Screening children for social determinants of health (SDOHs) has gained attention in recent years, but there is a deficit in understanding the present state of the science. OBJECTIVE To systematically review SDOH screening tools used with children, examine their psychometric properties, and evaluate how they detect early indicators of risk and inform care. DATA SOURCES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…This is the rst study reported in the scienti c literature to assess the feasibility and acceptability of SDOH screening and referral in a pediatric dental clinic of an FQHC network. Most research conducted to date on the topic of SDOH screening and referral has been in primary care, including reports related to SDOH screening tools, domains, processes, and guides for clinicians [21,[30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…This is the rst study reported in the scienti c literature to assess the feasibility and acceptability of SDOH screening and referral in a pediatric dental clinic of an FQHC network. Most research conducted to date on the topic of SDOH screening and referral has been in primary care, including reports related to SDOH screening tools, domains, processes, and guides for clinicians [21,[30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…The available evidence shows that the scope of services offered to patients in social prescribing schemes in the two countries have some similarities but also some notable differences (Figure 1). 14,25‐27 Programs in the United States typically concentrate on connecting patients to resources that help meet basic material needs, such as food insecurity and housing instability 28 . Services in England also help address patients’ basic social needs, as well as enabling social prescribing practitioners to refer patients to other types of services, such as arts and crafts and volunteering programs, whose purpose is to improve the patient's overall well‐being and quality of life.…”
Section: Figurementioning
confidence: 99%
“…For example, despite growing interest in trauma‐informed care, which considers how trauma affects development, trauma‐informed approaches are primarily implemented by persons within direct child‐serving systems (e.g., teachers, pediatricians, social workers (Herrenkohl et al., 2019)). Recently, efforts within health care and public health sectors have highlighted the need to address child trauma exposure and SDOH's, yet not all providers have such training (Garg et al., 2020; Garner et al., 2015; Herrenkohl et al., 2020; Sokol et al., 2019). Although not all members of the child‐serving ecosystem can become trauma‐informed care providers or IMH specialists, knowledge regarding the science of early development may be important in informing decision‐making across sectors that directly or indirectly impact children and families.…”
Section: Need For Relationally and Developmentally Informed Systems A...mentioning
confidence: 99%
“…WE CARE is a clinic‐based SDOH screening and referral system developed for pediatric settings, and it has been implemented with parents of children ages 0–5 years (Garg et al., 2015). SDOH screening and referral could occur in a variety of settings (e.g., daycares, workplaces) but pediatric settings are the most common to date (Sokol et al., 2019). WE CARE includes three core activities.…”
Section: A Developmentally‐ and Relationally‐informed Model For Cross...mentioning
confidence: 99%